HUBUNGAN PENGALAMAN BELAJAR BIOLOGI REPRODUKSI MANUSIA TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN LITERASI KESEHATAN REPRODUKSI(THE RELATIONSHIP BETWEEN LEARNING EXPERIENCES IN HUMAN REPRODUCTION AND HIGH SCHOOL STUDENTS’ CRITICAL THINKING SKILLS AND REPRODUCTIVE HEALTH LITERACY) - Abdillah, Yasri; Pertiwi, Kartika Ratna (Universitas Negeri Yogyakarta, 2025)
The rapid development of ICT makes it easy for teenagers to access pornographic content. Therefore, critical thinking skills and health literacy are essential so teenagers can effectively filter the information they access. This study aims to determine the level of learning experience of human reproduction material, critical thinking skills, and reproductive health literacy, as well as the relationship between learning experience of human reproduction material and critical thinking skills, the relationship between learning experience of human reproduction material and reproductive health literacy, the relationship between critical thinking skills and reproductive health literacy. This study is a cross-sectional observational study. The sample was selected using cluster random sampling. The results of the sample selection were for two classes, X and XI. Data collection was carried out using questionnaires, tests, and interviews. Instrument validity was carried out using expert judgment. Data were analyzed descriptively. At the same time, the hypothesis test used the chi-square test. The results of the study, namely: (1) the medium category dominates learning experiences, (2) the low category dominates critical thinking, (3) reproductive health literacy in class is dominated by the medium category, (4) based on the chi-square test on learning experiences with critical thinking, a significance value of 0.265 was obtained (5) based on the chi-square test on learning experiences with reproductive health literacy, a significance value of 0.037 was obtained (6) based on the chi-square test on critical thinking skills with reproductive health literacy, a significance value of 0.865 was obtained. It can be concluded that there is no significant relationship between learning experiences of reproductive material and critical thinking, nor between reproductive health literacy and critical thinking; however, a significant relationship was found between learning experiences of reproductive material and reproductive health literacy.